Framing perspectives: Frames Conservation and Reframing at the National Gallery of Victoria. Issue 2 (3rd July 2017) - McGowan-Jackson, Holly
Abstract : This paper discusses changing attitudes to picture frames during the twentieth century at the National Gallery of Victoria. By the 1990s frames conservation, research and reframing were areas of focus for the institution. The approaches and methods developed at the National Gallery of Victoria while addressing the framing needs of the collection over the past two decades are outlined, with examples provided by three case studies. This includes the introduction of innovative methods of communicating information about frames and their conservation, to staff, volunteers and visitors, both in the gallery and on-line.